Environmental port management: Conceptual model development and use of tools to evaluate and monitor dredging activities in the Port of Rio Grande, Brazil - J. Ronaldo Torres; L. Antônio Philomena (African Journal of Environmental Economics and Management, 2013)
This work concerns assessing and monitoring of dredging activities in the Port of Rio Grande, Brazil. The subject is presented to address the major problems related to the dredging process itself and sediment disposal options. From the dredging works carried out in 1998, 2000 and 2003 on the Port of Rio Grande, different data were gathered and used to develop a preliminary conceptual model of this process. The conceptual model elaborated and presented in this study consists of technical, ecological and socio-economic aspects of dredging. This model, which is an analysis of the major points to be considered when dealing with dredging projects at the Port of Rio Grande, highlights the importance of monitoring these activities from all aspects. The main points to be considered are: Selecting the type of dredge and the method of management and disposal of the sediments; monitoring the impacts within the environment (plants, animals, water and sediment quality), and the operational and monitoring costs of these activities. Another point that should be considered is about the disposal options or beneficial reuse of the dredged material.